(untitled) - Hartley, Bernard (New York, 1996)
This book is designed to follow "Departures" and "Connections", consolidating and building upon the oral skills. The material consists of 80 units, each clearly laid out on a separate page. The Teacher's Book contains the complete Student Book interleaved with detailed teaching notes. These give step-by-step instructions for using the material, ideas for additional activities, and comprehensive suggestions on how to present each new topic
Keywords: Americanism,English language,English language; United States